Citogenética básica e molecular em espécies de pimelodidae (siluriformes) coletadas nas bacias do rio paraná e do rio uruguai: uma abordagem na taxonomia e sistemática. - Girardi, Simone Cristina (2015)
Pimelodidae is a family of fishes of South America, and although several taxonomic and molecular studies have been conducted, the phylogenetic relationships among the genera are not still fully understood. In order to provide data to assist in the understanding of the relationships within this family, cytogenetic studies were performed in two species of Iheringichthys and seven species of Pimelodus from three river systems. The specimens were collected in the Piquiri River, Upper Paraná River basin; in the Iguaçu River, downstream to the Iguaçu Falls in the Middle Paraná River basin; in the Iguaçu River, Lower Iguaçu River basin and in the Ijuí River, Upper Uruguay River basin. The analysis showed the presence of 2n=56 chromosomes for all species, corroborating the hypothesis of this basal diploid number for the family. The AgNORs, confirmed by 18S rDNA-FISH, were localized in the terminal position on long arm of a chromosome pair for all analyzed species, which has been reported for all species of Pimelodidae and may indicate a basal trait for the family. The heterochromatin distribution pattern found herein is similar to those described for other Pimelodidae, and allowed us to differentiate most of the species, becoming an important marker. The location of 5S rDNA sequences in Iheringichthys species allowed their differentiation, and can be used as a taxonomic marker. In Pimelodus species, it was verified a variation in the number and position of 5S rDNA sites. In P. britskii and P. maculates, sites of 5S rDNA and 18S were found in synteny, which may indicate a derived condition for these species, considering that they are the only for pimelodids species till now studied that have this feature. The results of this study provided data that contribute to the knowledge of the evolutionary history of the species for Pimelodidae; establishing phylogenetic relationships and assisting in the identification of these species.